Strategi Pengembangan Diri Mahasiswa Melalui Kurikulum Merdeka Belajar untuk Meningkatkan Kemampuan Berbicara di Jurusan Pendidikan Bahasa Arab FTK UIN Mataram - Amalia Rahajeng Wulandari; Suparmanto Suparmanto; Vina Ri’ayatillah; Iska Rahmatul Wipqi; Marina Ishak (Al-TARQIYAH: Jurnal Pendidikan Bahasa Arab, 2023)
This research discusses self-development strategies for students through the Merdeka Belajar curriculum, focusing on improving speaking skills in the Arabic Language Education department of the Faculty of Tarbiyah and Teacher Training at UIN Mataram. The aim of this research is to determine the impact of the implementation of the new curriculum on the development of students' speaking competencies. The research method employed is a descriptive qualitative approach, and data collection is done through triangulation, involving observation, interviews, and documentation. The strategies used by students in developing their speaking skills are diverse. The research results indicate that students have their own strategies in efforts to enhance their speaking skills. Some students participate in organizations and additional classes for this purpose.